Impact of Permitted Driving Speed on the Design of Urban Street Network in Latvia - Ziedonis Lazda; Juris Smirnovs (The Baltic Journal of Road and Bridge Engineering, 2011)
Today, an increasing number of necessary infrastructural measures is encountered the purpose of which is to assist in managing the traffic speed thus forming the most important part in speed management policies. This paper reviews the choice of permitted driving speed depending on the defined street category. The existing norms that define road functions and categories for the urban street network in Latvia are evaluated. This paper stresses the need to review the functional classification of the road network with specific attention paid to the importance of each road type and their influence on the drivers’ choice of adequate driving speed. A practical study on the efficiency of the chosen road profile (number of lanes, median, etc.) and design parametres (width of driving lanes, longitudinal curvature radius, horizontal curvature radius, etc.) in the existing street network has been performed.